2016
DOI: 10.1177/0959683616670217
|View full text |Cite
|
Sign up to set email alerts
|

Holocene biogeography of Tsuga mertensiana and other conifers in the Kenai Mountains and Prince William Sound, south-central Alaska

Abstract: Several important North American coastal conifers – having immigrated during the Holocene from the southeast – reach their northern and upper elevation limits in south-central Alaska. However, our understanding of the specific timing of migration has been incomplete. Here, we use two new pollen profiles from a coastal and a high-elevation site in the Eastern Kenai Peninsula–Prince William Sound region, along with other published pollen records, to investigate the Holocene biogeography and development history o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(23 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…() suggested that Picea may have arrived even earlier (11.0–10.0 ka) at Swanson Fen. The tree moved slowly south, so that it occurred throughout the Kenai Mountains by ~6.5–6.0 ka, ~6.0 ka in the southern Caribou Hills (Circle Lake), and reaching its southernmost Kenai Peninsula site (Homer Spit) by ~5000 years ago (Ager, ; summarized in Anderson et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…() suggested that Picea may have arrived even earlier (11.0–10.0 ka) at Swanson Fen. The tree moved slowly south, so that it occurred throughout the Kenai Mountains by ~6.5–6.0 ka, ~6.0 ka in the southern Caribou Hills (Circle Lake), and reaching its southernmost Kenai Peninsula site (Homer Spit) by ~5000 years ago (Ager, ; summarized in Anderson et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…The record from the coastal Mica Lake stands alone in contrast to this pattern, with two different conifers – Tsuga mertensiana and Picea sitchensis –establishing there by~6.0 and ~5.0 ka, respectively (Fig. ; Anderson et al ., ). These ages represent the earliest establishment of these two conifers on the Kenai Peninsula, and this site could well have served as a node for subsequent expansion both to the west and to the east.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations